Workers Like All the Rest of Them Domestic Service and the Rights of Labor in Twentieth-Century Chile - Hutchison, Elizabeth Quay (Duke University Press, 2022)
In Workers Like All the Rest of Them, Elizabeth Quay Hutchison recounts the long struggle for domestic workers' recognition and rights in Chile across the twentieth century. Hutchison traces the legal and social history of domestic workers and their rights, outlining their transition from slavery to servitude. For most of the twentieth century, domestic service remained one of the key "underdeveloped" sectors in Chile's modernizing economy. Hutchison argues that the predominance of women in that underpaid, under-regulated labor sector provides one key to persistent gender and class inequality. Through archival research, firsthand accounts, and interviews with veteran activists, Hutchison challenges domestic workers' exclusion from Chilean history and reveals how and under what conditions they mobilized for change, forging alliances with everyone from Church leaders and legislators to feminists and political party leaders. Hutchison contributes to a growing global conversation among activists and scholars about domestic workers' rights, providing a lens for understanding how the changing structure of domestic work and worker activism have both perpetuated and challenged forms of ethnic, gender, and social inequality.